THE RESULTS OF THE KORENIZATION POLICY IN THE NORTH CAUCASUS BY THE MIDDLE 1930s – EARLY 1940s - E. A. GUNAEV (Кавказология, 2021)
The policy of “korenization” carried out by the Soviet government in the 1920s – 1930s had its own peculiarities in the North Caucasus, due to the complex historical past of integration into a single Russian political and legal space and the ethnic diversity of the region. Mass korenization in the North Caucasus began later than the rest of the country's regions, it was officially announced in 1929. Russian historiography notes that this process was accompanied by both objective (low literacy rate, alertness of the local population, interethnic tension, armed resistance to the Soviet government) and subjective difficulties (organizational and managerial problems). Korenization was far from complete by the beginning of the 1940s. Mass repressions against the leadership of the national cadres, the national intelligentsia of the late 1930s also played a negative role.